From Theory to Classroom: Implementing Translanguaging Pedagogy for Refugee Learners - See, Jasmine; Asmawi, Adelina Binti (Refuge)

(untitled) (Centre for Refugee Studies, York University, 2025)
This study bridges the gap between theoretical frameworks and classroom practice by designing a translanguaging pedagogy (TP) module for volunteer teachers at an alternative learning centre serving refugees in Malaysia. Grounded in a comprehensive needs analysis and refined through expert consensus, the module emphasizes bilingual proficiency, interactive teaching methods, and diverse learning materials to enhance English communication skills. Focused on pedagogical usability and teacher engagement, the research evaluates the module’s effectiveness through teachers’ perceptions and interactions with students, rather than language proficiency outcomes. Findings demonstrate TP offers a practical, inclusive approach to meeting refugee learners’ unique needs, contributing to the development of adaptable, effective teaching strategies that translate theory into impactful classroom practices for marginalized communities.